Psychological distress, hopelessness and health service needs of late adolescents in rural Pondicherry, South India - Niranjjan, R.; Sarkar, Sonali; Balajee, Karthik; Srinivasan, Manikandan (International Journal Of Community Medicine And Public Health, 2018)
Background: Late adolescence (15-19 years) is a period which entails stress and specific physical and mental health needs. The Objectives were to study the prevalence of psychological distress, hopelessness, and health service needs of late adolescence in rural Puducherry. Methods: A community based cross-sectional study was conducted in a service practice area of Jawaharlal Institute Rural Health centre (JIRHC) during July-August 2015. A pretested questionnaire was used to obtain demographic characteristics, health service needs and substance abuse among adolescents and their family members. Self-administered GHQ-12 questionnaire and becks hopelessness scale was used to assess the psychological distress and hopelessness respectively. Results: Of the total 324 participants, 170 (53%) were females. The mean (SD) age was 15.9 (1.3) years. One fifth of the adolescents (20.9%) had psychological distress. Moderate level of hopelessness was seen in 32 (10%) adolescents. Substance abuse was found in 125 (39%) of the family members of adolescents and 55 (44%) had problems at home related to the substance abuse. On multivariate analysis, problem in household due to substance abuse was the single independent risk factor [aOR 2.6; 95%CI (1.1-6.0)] for psychological distress. Majority of females expressed their need for an exclusive adolescent clinic (58%), sexual & reproductive awareness (67.5%) and information about contraception (67.4%). The need for mental health services was higher in females compared to males (55.6% vs. 44.3%), which was statistically significant (p<0.05). Conclusions: In rural area of Puducherry, one out of five adolescents had psychological distress and ten percentages of adolescents had moderate level of hopelessness requiring mental health and counselling services.